PENGARUH DUKUNGAN SUAMI DAN DUKUNGAN KELUARGA TERHADAP IBU YANG MENGALAMI BABY BLUES DI DESA SEUAT JAYA SERANG BANTEN - Agustini, Elsa Siti; Hasrida (Bina Generasi : Jurnal Kesehatan, 2025)
Postpartum blues in Indonesia is ranked fourth, namely around 31 births per 1000 population. If this incident is not handled immediately, it will progress to the next stage, namely the depression stage and then the psychotic stage. Baby blues syndrome can be overcome by having open communication with your husband or family. The aim of this research is to analyze the influence of husband's support and family support on the incidence of baby blues in post partum mothers. This type of research is a cross sectional research design. The location used for this research is “Seuat Jaya” Village, Serang - Banten from December 2023 to January 2024. The sample used in this research used total sampling with a minimum sample of 30 people. The dependent variable in this research is the incidence of baby blues syndrome and the independent variables are husband's support and family support. The bivariate analysis used in this research was the chi square test. The results of the chi square analysis show a p value of 0.004, so there is a significant influence between good husband support and the incidence of baby blues syndrome. The p value is 0.006, so it can be concluded that there is a significant influence between good family support and the incidence of baby blues syndrome